------------------------------------------------------------------
General Formula
------------------------------------------------------------------
y = mx + b
------------------------------------------------------------------
Substitute the value of m and b
------------------------------------------------------------------
y = -3x - 1/2
Alternatively, if we rearrange the terms, it can be:
y + 3x + 1/2 = 0 OR 2y + 6x + 1 = 0
------------------------------------------------------------------
Answer : y = -3x - 1/2
------------------------------------------------------------------